ANALISIS NILAI-NILAI KEHIDUPAN DAN KARAKTER TOKOH DALAM NOVEL SANDIWARA LANGIT KARYA ABU UMAR BASYIER (KAJIAN PRAGMATIK) - Adawiyah, Rabiyatul (Institut Pendidikan Tapanuli Selatan, 2018)
The problem in this study is how the value of life and character of the characters in the novel Sandiwara Langit by Abu Umar Basyier in terms of pragmatic ?. The purpose of this study is to describe the value of life and character of the characters in the novel Sandiwara Langit by Abu Umar Basyier in terms of pragmatic. Qualitative research method is a method commonly used in the types of social science research, humanities, and the science of law. Research on a literary work is a research in the realm of humanities. That is the reason the qualitative method is appropriately used in the research process of the novel Sandiwara Langit by Abu Umar Basyier. In addition, qualitative methods can provide detailed details about unknown phenomena in the object of research. Sources of data in this study is a novel Sandiwara Langit by Abu Umar Basyier which amounted to 211 pages. The results of the data analysis concluded that the value of life and character of the characters in the novel Sandiwara Langit by Abu Umar Basyier pragmatic views in terms of 1) the religious / religious values ââof religious values ââcontained in the novel depicted on the figure of Rizqaan who always cling to the teachings of religion and he always apply religious values ââto their daily life, 2) cultural values ââthat is the existence of special vocations between husband and wife that will make them closer and their relationship more harmonious, 3) moral value that is the value depicted on the figure of Rizqaan and Halimah who is a steadfast, obedient and obedient husband and wife and 4) Social value is a value that refers to the relationship of individuals with other individuals in a society. How one should behave, how they solve problems, and deal with certain situations are also included in social values.